MUNICIPALITY ELECTIONS IN LATVIA: ANALYSIS OF PRE-ELECTION PROGRAMS - Ozolzīle, Gunārs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The object of the research is the election of municipal governments (for cities of republican significance). The pre-election programmes of political parties, their associations and coalitions are analysed in the paper. The novelty of the research is determined by the fact that only pre-election programmes of political parties elaborated for the Saeima elections have been studied in Latvia so far, but there is no similar study on municipal elections. Voters, having become familiar with pre-election programmes of political parties, often recognise that these documents contain many uncertain and impossible promises. Assuming that the “quality” of party programmes could affect voter turnout and, consequently, the election results, it is possible to formulate the research problem: a different level of the specificity of the party pre-election programmes and its possible relation to the election results. In the research, by specificity (we will use this concept for the sake of convenience) we imply the relation between the number of promises, which can be assessed as concrete and realistic, and the total number of promises in the pre-election programmes. However, the aim of the research is to investigate the level of specificity of the party pre-election programmes and determine its relation to the results of the parties in municipal elections. The method of the content analysis has been used to evaluate the pre-election programmes. To achieve the aim of the research and determine whether there is a correlation between the level of specificity of the pre-election programmes and the results of the parties (votes obtained) in the municipal elections, Spearman’s rank correlation coefficient is used. In all cities (except two), the correlation between the two variables is markedly weak or even with a minus sign.